Estudo das alterações no potencial de repouso neuronal induzidas por prostaglandina E2 em culturas primárias de gânglio da raiz dorsal de ratos por meio de microscopia de fluorescência - Santos, Débora de Oliveira (2018)
Introduction: Prostaglandin E2 (PGE2) is an inflammatory mediator able to sensitize peripheral sensory neurons and cause hyperalgesia. Studies suggests that the molecular mechanism involved in the sensitization by PGE2 is dependent on the activation of adenylate cyclase/cAMP/PKA pathway, and also, modifications in ion channels, as potassium channels (K+). Objectives: Study the depolarization induced by PGE2 in cultures of primary sensory neurons using fluorescence microscopy, as a possible model for studies of sensitization of nociceptors and evaluate the involvement of K+ channels in this process. Materials and Methods: Primary cultures of neurons were cultivated from the dorsal root ganglia (DRG) of adult rats and variations in membrane potential were recorded by confocal microscopy through variation of fluorescence emitted by neurons in the presence of DiBAC4(3) indicator. The effect of administration of PGE2, db-cAMP (cAMP analogue), H89 (PKA inhibitor), morphine and the K+ channel blockers: glibenclemida, TEA and 4-AP were evaluated. Also, the membrane potential of neurons isolated from animals treated in vivo by intraplantar injection of PGE2 were evaluated Results: The PGE2 (1, 10 and 100 nM) depolarized neurons of concentration-dependent manner, and this effect occurred predominantly in neurons of smaller diameter (10 to 20 µm). In addition, in cultures of neurons obtained from dorsal root ganglia (L4 and L5) ipsilateral to the treatment by intraplantar with PGE2 (100 ng) in rats, there was a depolarized resting potential in relation to isolated neurons of contralateral ganglia of the same animals, evidencing a correlation between the effect in vivo and in vitro of PGE2. With regard to the involvement of adenylate cyclase/cAMP/PKA in the sensitization of sensory neurons by PGE2, it was noticed that the administration of db-cAMP induced depolarization in a similar manner to the ones observed with PGE2 (100 nM) and that the depolarization induced by PGE2 is inhibited in the presence of H89. Also the effects of selective inhibitors of K+ channels were tested and it was observed that 4-AP, a type A channel blocker, depolarized neurons in a similar manner to PGE2. In addition, it was observed that the PGE2 shows no effect after depolarization induced by 4-AP and it also does not alter the membrane potential of neurons previously despolarizadas by PGE2. These results indicate that PGE2 and 4-AP acts on the same K+ channels. The effect of morphine was also tested, an analgesic whose peripheral effect is dependent on the opening of K+ channels sensitive to ATP, and the results have shown that morphine inhibits depolarization induced by PGE2 and also by 4-AP, evidencing that PGE2 and morphine act on different K+ channels. Conclusion: In conclusion, the PGE2 depolirized DRG neurons in a concentration – dependent manner and the results suggest that the subjancente mechanism to this sensitization involves the activation of cAMP/PKA and the inhibition of K+ currents type A. The proposed in vitro model for the study of peripheral sensitization shows similar results found in other experimental models and can contribute to the understanding of nociceptive sensitization and development of drugs with analgesic action.